(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this article we find the fïnite sum of reciprocal k-Fibonacci numbers of subscript 2n a, then we fïnd the infinite sum of these numbers. Special cases of these sums for the classical Fibonacci sequence and the Pell sequence are indicated. Finally we propose a new way to fïnd the infinite sum of the reciprocal k-Fibonacci numbers with odd subscripts and, consequently, the sum of all reciprocal k-Fibonacci numbers, but without finding the answer to this problem (Erdos).